Genomics into Healthcare: The 5th Pan Arab Human Genetics Conference and 2013 Golden Helix Symposium. Issue 5 (31st March 2014) - Fortina, Paolo; Khaja, Najib Al; Ali, Mahmoud Taleb Al; Hamzeh, Abdul Rezzak; Nair, Pratibha; Innocenti, Federico; Patrinos, George P.; Kricka, Larry J.
ABSTRACT The joint 5th Pan Arab Human Genetics conference and 2013 Golden Helix Symposium, "Genomics into Healthcare" was coorganized by the Center for Arab Genomic Studies (http://www.cags.org.ae) in collaboration with the Golden Helix Foundation (http://www.goldenhelix.org) in Dubai, United Arab Emirates from 17 to 19 November, 2013. The meeting was attended by over 900 participants, doctors and biomedical students from over 50 countries and was organized into a series of nine themed sessions that covered cancer genomics and epigenetics, genomic and epigenetic studies, genomics of blood and metabolic disorders, cytogenetic diagnosis and molecular profiling, next‐generation sequencing, consanguinity and hereditary diseases, clinical genomics, clinical applications of pharmacogenomics, and genomics in public health.